Removal of phosphates from aqueous solutions by using bauxite: I. effect of pH on the adsorption of various phosphates - Altundoğan, Hamdi Soner; Tümen, Fikret (My University, 2002)
In this study, the effect of pH on adsorption of various forms of phosphate onto bauxite was investigated. For this purpose, the adsorption and desorption of inorganic (ortho and condensed) and organic phosphate species were studied. It was observed that the adsorption tendency of the various phosphate forms was different and depended on pH. Maximum adsorption efficiencies for all phosphate forms were achieved in slightly acidic conditions (pH 3.2–5.5). The results of adsorption and desorption studies showed that the adsorption of phosphates onto bauxite is based on a ligand exchange mechanism. The adsorption mechanism of inorganic condensed phosphates and organic phosphates is thought to be more complex than that of orthophosphate. It can be stated that the adsorption of organic phosphates is dependent on the functionality, number, and variety of organic groups. The results of experiments carried out with mixed phosphate solutions showed that the adsorption yields of various phosphate forms are dependent on the composition of the solution. The relative adsorptivity of various phosphates was found to be in the general order of hexametaphosphate?>?pyrophosphate?> orthophosphate?>?tripolyphosphate?>?adenosine triphosphate?>?glycerophosphate?>?glucose-1-phosphate.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Phosphate adsorption; Bauxite; Adsorption of mixed phosphates; Surface complexation